Evidence-based Bundles and Cesarean Delivery Surgical Site Infections: A Systematic Review and Meta-Analysis. Issue 1 (March 2018) - Carter, E.B.; Temming, L.A.; Fowler, S.; Eppes, C.; Gross, G.; Srinivas, S.K.; Macones, G.A.; Colditz, G.A.; Tuuli, M.G.
Abstract : ( Obstet Gynecol . 2017;130(4):735–746) Cesarean delivery surgical site infections can result in significant maternal morbidity, including increased length of stay, readmission, cost, and emotional burden. Identified interventions that may reduce risk are antibiotic prophylaxis before incision, extended-spectrum prophylaxis, chlorhexidine-alcohol skin preparation, placental removal via gentle traction, subcutaneous closure, and use of sutures instead of staples. In this study, the authors conducted a systematic review and meta-analysis to estimate whether bundles (combinations of 3 or more of these evidence-based interventions) were associated with an even greater reduction in risk.